"How Do We Know It's Working?": The Teaching Artist's Role in Program Evaluations and Assessing Student Work. Issue 2 (2nd April 2016) - Brown, Martha A.
ABSTRACT: This article provides a framework to assist evaluators, teaching artists, and program managers in working together.